REPRESENTASI POLITIK DALAM NOVEL KALATIDHA KARYA SENO GUMIRA AJIDARMA - Setiawan, Teguh Putra; Hayati, Yenni; Nst., Muhammad Ismail (Universitas Negeri Padang, 2018)
The type of this research is qualitative research using descriptive analysis method. The object of this research is the novel by Kalatidha Seno Gumira Ajidarma. The completion technique of the data is done as follows. First, read and understand about the novel of Kalatidha by Seno Gumira Ajidarma. Second, to inventory the data related to political conflict, as well as the impact of conflict in Kalatidha's novel by Seno Gumira Ajidarma. Third, the grouping of the data that relatedÂ to indicators of political conflict, that is rulers between people in authority with society and both one society with the others and indicators of the causes of political conflict consisting of struggles and disputes, and the effects of political conflicts, namely culling, killing, torture, arson, detention without prosecuted, restriction, and defamation contained in Kalatidha's novel by Seno Gumira Ajidarma. The results of the research as follows. First, the political representation arises because the authors are not satisfied with the reality of political events, political conditions and political events of the New Orde regime of the G30S/PKI in Indonesia . The event is represented in the form of political conflict. The cause of political conflict between one society and another provoked by the policy of the authorities. Second factors that causing political conflict are caused by the struggle and opposition of the people toward the authorities. Third, the impact of political conflicts such as culling, killing, torture, arson, detention without prosecuted, restriction, and defamation.Keywords: representation, political, conflict, Kalatidha